Slavistika na Univerzi v Gradcu in slovenski doktorji filozofije 1870-1919 - Šivic-Dular, Alenka (Jezik in slovstvo, 2020)
From the establishment of the first professorship in Slavic philology in 1870 and the second (with a special emphasis on Slovenian language and literature) in 1896, to the vacating of these positions after the First World War, the following Slovenian professors taught at the University of Graz: Gregor Krek (1867-1902), Vatroslav Oblak (1892-1896), Karel Štrekelj (1896-1912), Matija Murko (1902-1917) and Rajko Nahtigal (1913-1919). However, after specialising in Slavic philology, only three Slovenians earned a doctorate with a dissertation in linguistics: Jakob Sket, Anton Breznik and Fran Ramovš. Among the younger PhD holders, only Ramovš pursued an academic career, while the professional and research activity of Sket and Breznik evolved in parallel with their careers as high school teachers. Even though they lived at different times and in different social and cultural conditions, they shared an awareness of the exceptional importance of education and the development of science in one's own language for the individual's cultural growth and the cultural advancement of the entire community. The Slovenians who had earned their doctorates in Graz and elsewhere around 1900 matured professionally to such an extent that after the establishment of Yugoslavia in 1918, they were able to vigorously advocate the establishment of the first Slovenian university. In the long term, this university irreversibly improved the Slovenian educational landscape, opening a path to a modern knowledge-based society.
Keywords: doktorati; jezikoslovje; linguistics; PhD holders; Slavic studies; slavistika; Slovenian studies; slovenistika; University of Graz; univerza v Gradcu